2012
DOI: 10.3892/ol.2012.842
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in disappearing colorectal cancer liver metastases during oxaliplatin-based chemotherapy

Abstract: Abstract. Some colorectal cancer liver metastases (CLMs) disappear on serial imaging during chemotherapy and the optimal treatment strategy for such lesions remains undetermined. The purpose of this study was to investigate the outcome in disappearing CLMs, as few studies have focused on this topic, with conflicting results. Among 125 patients with CLMs treated with modified FOLFOX6 with or without bevacizumab, those in whom all CLMs disappeared on computed tomography were identified. Recurrence of such disapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Conversion therapy for initially unresectable liver metastasis of CRC patients has a significant role. Some studies have claimed that in the process of conversion therapy, some liver lesions of 9-37% patients with CRLM are not visible on the radiology, known as DLM [2,6,[21][22][23]. This study shows DLM in 31.0% of 113 patients, similar to the previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…Conversion therapy for initially unresectable liver metastasis of CRC patients has a significant role. Some studies have claimed that in the process of conversion therapy, some liver lesions of 9-37% patients with CRLM are not visible on the radiology, known as DLM [2,6,[21][22][23]. This study shows DLM in 31.0% of 113 patients, similar to the previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest that DLMs should be resected when detected by sequential inspection using EOB-MRI and CE-IOUS that visualize DLMs containing residual tumors. It has been controversial whether to resect all DLMs because the reported incidence of viable DLMs is variable, ranging from 0% to 80%, 1,2,4,15,16 and because no diagnostic modalities that specify viable DLMs have been available. The authors have previously reported 97% accuracy of CE-IOUS to identify histologically confirmed CRLMs among tumors detected on imaging studies, 11 and the current study went a step further by showing 83% accuracy of CE-IOUS to identify viable DLMs among DLMs on CE-CT.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Though a complete radiologic response does not guarantee a durable or complete pathologic response, there are some studies that report a complete pathological response or no evidence of in situ recurrence ranging from 16.7 to 80.5%. 7,19,23,31 The findings of this survey allow for surgeons to place their own practices in the context of their colleagues in many different countries and continents and perhaps to adjust their practices to align with what is being done in most centers. Most significantly, only 47% of surgeons in this survey use MRI for preoperative planning though there is evolving data that MRI is superior to CT or PET.…”
Section: Discussionmentioning
confidence: 99%